THE EFFECT OF COMPANY SERVICE QUALITY AND IMAGE TO THE SATISFACTION OF BPJS KETENAGAKERJAAN USERS - Dimas Willy Prayoga (Universitas muhammadiyah malang, 2019)
BPJS Ketenagakerjaan insurance participants always increase, but the level of user satisfaction always shows unstable. The level of service quality applied by BPJS has not optimal it can be seen from the level of complaints to BPJS services and also the BPJS’s awareness index ranks to be lowest. BPJS Ketenagakerjaan must rebuild the company's image to become top of mind in the community due to the transformation process. That kind of condition can obstruct the company development and also affect the company's image. This research aimed to determine the effect of service quality and corporate image on service satisfaction of BPJS Ketenagakerjaan. This study was a descriptive study using a quantitative approach. This study has conducted a survey using questionnaires as the research instrument to gather the data. The population of this study was BPJS Ketenagakerjaan costumers who were ever visited and used the facilities at the BPJS Ketenagakerjaan office. The total sample of this study were 300 respondents employing incidental sampling. The data analysis used is descriptive analysis and path analysis. This study found that there is a positive correlation between service quality and company image. There is also a significant partial effect of satisfaction on service quality. There is a partial effect of the company image on service satisfaction. Then, there is a significant and positive simultaneous effect of service quality and company image on the service satisfaction of BPJS Ketenagakerjaan.